Skeletal muscle-kidney crosstalk in a cohort of critical illness survivors - Heitor S. Ribeiro; Dário R. Mondini; Guilherme P. Santa-Catharina; Lia Marçal; Leila Antonângelo; Luis Yu; Dirce M. T. Zanetta; Linamara R. Battistella; Geraldo F. Busatto; Carlos R. R. Carvalho; Emmanuel A. Burdmann (PLoS ONE, 2026)
Background The skeletal muscles and kidneys are frequently affected during critical illness; however, their crosstalk remains poorly explored, especially in the long-term evolution. Therefore, we investigated the crosstalk between skeletal muscle and kidney function in COVID-19 survivors. Methods A cross-sectional analysis of a prospective cohort study with s urvivors of moderate to severe COVID-19 hospitalization. Skeletal muscle assessments included handgrip strength, calf circumference, ultrasound-measured quadriceps thickness, and gait speed test. Sarcopenia was diagnosed by modified EWGSOP2 (low handgrip strength plus low ultrasound-measured quadriceps thickness). Kidney function was assessed by estimated glomerular filtration rate (eGFR), urinary albumin-to-creatinine ratio (UACR), and urine sediment analysis. Abnormal kidney function was defined as an eGFR < 60 mL/min/1.73m 2 , albuminuria (≥30 mg/g), and/or leukocyturia or hematuria. Results A total of 734 survivors (46% female, 43% ≥ 60 years, 35% with diabetes) were assessed 7 ± 2 months post-hospital discharge. Sarcopenia was diagnosed in 21.4% of the cohort. Positive significant associations with eGFR were observed for calf circumference (β = 0.42 ml/min/1.73m 2 , 95%CI: 0.06 to 0.78) and thicknesses (mm) of rectus femoris (β = 0.47, 95%CI: 0.01 to 0.94) and vastus intermedius (β = 0.55, 95%CI: 0.14 to 0.96). None of the skeletal muscle parameters were associated with UACR (mg/g). Survivors with sarcopenia had lower eGFR (‒5.8 ml/min/1.73m 2 , 95%CI: ‒10.8 to ‒0.9), but similar frequencies of low eGFR (24% vs . 18%; p = 0.137), albuminuria (27% vs . 31%; p = 0.434) and abnormal urine sediment (17% vs . 22%; p = 0.217) as compared to those without sarcopenia. Sarcopenia was not associated with higher odds of low eGFR, albuminuria, or abnormal urine sediment. Conclusions In survivors of moderate to severe COVID-19 hospitalization, skeletal muscle mass was associated with eGFR, whereas sarcopenia per se was not independently associated with poor kidney function. These findings suggest the existence of a skeletal muscle-kidney crosstalk in this population.